Mycobacterial ESAT-6 and katG are Recognized by Sarcoidosis CD4+ T Cells When Presented by the American Sarcoidosis Susceptibility Allele, DRB1*1101 - Oswald-Richter, Kyra (Springer US, 2009)
INTRODUCTION: Genetic associations of American sarcoidosis susceptibility implicate MHC class II allele, DRB1*1101. We previously reported immune recognition of Mycobacterium peptides from peripheral cells of 26 sarcoidosis subjects, 24 PPD− healthy volunteers, and eight with latent tuberculosis infection. MATERIALS AND METHODS: In order to further link these genetic and immunologic pillars of sarcoidosis pathogenesis, we performed flow cytometry on these same subjects to identify the cells responsible for immune responses to ESAT-6 and katG peptides, followed by HLA typing to determine allelic associations with recognition. DISCUSSION AND CONCLUSION: Sarcoidosis CD4+ T cells were primarily responsible for the systemic responses. Recognition was inhibited by monoclonal antibody against HLA-DR and HLA-DQ, but not HLA-DP. Immune recognition of ESAT-6 peptide NNALQNLARTISEAG was associated with possession of DRB1*1101. ESAT-6 and katG presented by antigen-presenting cells expressing DRB1*1101-induced Th-1 responses from sarcoidosis T cells, thus providing a mechanistic insight for the association of HLA DRB1*1101 with sarcoidosis, and sarcoidosis T cell interaction with microbial antigens.